A mixed methods evaluation of a two-day cognitive behavioural therapy workshop for medicines-related consultations - White, D (2021)
Medication adherence describes the health-related behaviour of the ingestion of medicines by those prescribed them, and in the manner prescribed by their Health Care Professionals. Non-adherence and poor adherence to medication regimes is a common, highly complex problem that contributes to substantial worsening of disease, death and increased healthcare costs. In 2003 the World Health Organization (WHO) declared it a major public health concern. There is a known psychological component to non-adherence and rates of non-adherence have been associated with patients’ beliefs about medication, specifically doubts about the need for medicines and concerns regarding their use. There are no clear-cut, universally recommended, evidence-based guidelines or strategies to tackle the problem of adherence, but there is evidence to suggest that successful interventions often contain both cognitive and behavioural components, and when these are combined with traditional approaches (reminders and pill boxes etc.), outperform them. A novel intervention aimed at addressing non-adherence was designed using principles and techniques drawn, primarily, from Cognitive Behavioural Therapy (CBT), which could be delivered by healthcare professionals (HCPs) during routine consultations with patients about medicines. The intervention was taught to 93 HCPs. It was evaluated using parallel-design mixed methods, and utilised existing models for evaluating training impact, assessing various stages of outcome. Numerous quantitative and qualitative investigations revealed that HCPs were highly satisfied with the course, that their knowledge and skills statistically significantly improved and that this effect lasted for at least 6-months. Furthermore, aspects of job satisfaction statistically significantly improved from the beginning to the end of the course. Qualitative investigations at 6-months reported behavioural change amongst course attendees leading to helpful, productive consultations with their patients. Patients who had received a consultation with trained HCPs found them to useful and empowering with regards to choices and actions about their health and treatment. The final study failed to demonstrate a statistically significant improvement in self-reported adherence or beliefs change in regard to prescribed medication but showed trends that warrant further investigation.